Childhood myopia and parental smoking. Issue 7 (17th June 2004) - Saw, S-M; Chia, K-S; Lindstrom, J M; Tan, D T H; Stone, R A
Abstract : Aim: To examine the relation between exposure to passive parental smoke and myopia in Chinese children in Singapore. Methods: 1334 Chinese children from three schools in Singapore were recruited, all of whom were participants in the Singapore Cohort study Of the Risk factors for Myopia (SCORM). Information on whether the father or mother smoked, number of years smoked, and the number of cigarettes smoked per day during the child's lifetime were derived. These data were correlated with contemporaneously obtained data available in SCORM. The children's cycloplegic autorefraction, corneal curvature radius, and biometry measures were compared with reported parental smoking history. Results: There were 434 fathers (33.3%) and 23 mothers (1.7%) who smoked during their child's lifetime. There were no significant trends observed between paternal smoking and refractive error or axial length. After controlling for age, sex, school, mother's education, and mother's myopia, children with mothers who had ever smoked during their lifetime had more "positive" refractions (adjusted mean −0.28 D v −1.38 D) compared with children whose mother did not smoke (p = 0.012). Conclusions: The study found no consistent evidence of association between parental smoking and refractive error. There was a suggestion that children whose mothers smoked cigarettes had more hyperopic refractions, but the absence of a relation with paternal smoking and the small number of mothers who smoked in this sample preclude definite conclusions about a link between passive smoking exposure and myopia.